2020
DOI: 10.1111/ene.14491
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine release syndrome‐associated encephalopathy in patients with COVID‐19

Abstract: Background Neurological manifestations in coronavirus disease (COVID)‐2019 may adversely affect clinical outcomes. Severe COVID‐19 and uremia are risk factors for neurological complications. However, the lack of insight into their pathogenesis, particularly with respect to the role of the cytokine release syndrome (CRS), is currently hampering effective therapeutic interventions. Methods In this longitudinal study, we sought to describe the neurological manifestations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
197
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(203 citation statements)
references
References 28 publications
4
197
0
2
Order By: Relevance
“…Neurological short-term prognosis was available for 26 patients in the case reports ( Table 3 ) or case series [29] , [32] , [33] and 116 patients in cohort studies [4] , [5] , [8] , [9] , [10] . A complete or partial recovery was noted in 109/142 patients (77%) either spontaneously ( n = 68) or with immunotherapy ( n = 41) including high-dose steroid treatment and/or intravenous immunoglobulins (IV Ig).…”
Section: Resultsmentioning
confidence: 99%
“…Neurological short-term prognosis was available for 26 patients in the case reports ( Table 3 ) or case series [29] , [32] , [33] and 116 patients in cohort studies [4] , [5] , [8] , [9] , [10] . A complete or partial recovery was noted in 109/142 patients (77%) either spontaneously ( n = 68) or with immunotherapy ( n = 41) including high-dose steroid treatment and/or intravenous immunoglobulins (IV Ig).…”
Section: Resultsmentioning
confidence: 99%
“…Although the CSF RBC count was only reported for 61/430 (14%) patients [ 22 , 28 , 29 , 31 , 35 , 39 , 40 , 44 , 73 , 74 , 77 , 78 , 81 , 89 , 92 , 102 , 110 , 118 , [120] , [121] , [122] , [123] , 128 , 133 , 134 , [138] , [139] , [140] , 156 , 165 , 166 , [172] , [173] , [174] , [175] , [176] , 180 , 184 , 188 , 191 , 192 , 198 , 202 , 204 , 208 , 215 , 220 , 225 , 227 , 233 , 241 , 242 , 246 ], the CSF white blood cell (WBC) count was provided for 409/430 (95%) patients, 270 (66%) of whom had >0 cells/μL, >1 WBC:1,000 RBC or were noted to have “pleocytosis” ( Fig. 3 ) [ [5] , [6] , [7] , [8] , 10 , 13 , [15] , [16] , [17] , [18] ...…”
Section: Resultsmentioning
confidence: 99%
“…Buzhdygan et al 69 found that SARS‐CoV‐2 spike protein could trigger a proinflammatory response on brain endothelial cells that may contribute to an altered state of BBB function. In an in vivo study, Perrin et al 70 found that serum levels of the astroglial marker, S100B protein, were increased at the time of cytokine release syndrome in COVID‐19 patient, reflecting an increased permeability of the BBB. These findings indicate that SARS‐CoV‐2 may also invade the CNS by impaired BBB.…”
Section: Discussionmentioning
confidence: 99%